HEGEMONY OF MODERNITY IN THE PRACTICE OF USADA BALI TREATMENT IN DENPASAR - Suatama, Ida Bagus; Anom Kumbara, A.A. Ngurah; Wirawan, A.A. Bagus; Arjani, Ni Luh (E-Journal of Cultural Studies, 2019)
The phenomenon of the hegemony of modernity in the practice treatment of Usada Bali in Denpasar City is interesting to observe. On the one hand, public interest in Usada Bali is still quite high, but also on the other hand modern medical dominance is so strong. Through a postmodernism approach and a qualitative method that relies on the workings of critical theory, its causes, forms, and implications, reveal this phenomenon. The cause of the hegemony of modernity is due to state regulation, the modern and traditional medical dichotomy, the disposition of rationality, and the expansion of material energy. The form of modernity hegemony includes the formalization of medical practices, identity mimesis, praxis of praxis awareness, and commodification of Usada Bali. The implications of the hegemony of modernity includes the strengthening of the existence of Usada Bali, the competition of health services, the reproduction of medical discourse, and the ambivalence of spirituality. This study found that modernity has more power, than traditional values. The discourse of development and empowerment of traditional medicine has not targeted Usada Bali as autonomous knowledge. The violations of sasana balian undoubtedly due to the strong influence of materialism. The existence of Usada Bali is in line with the community’s belief in the etiology of sakala and niskala. Keywords: Hegemony, Modernity, Practice of Medicine, Usada Bali